Effects of General Instructions on Rule Following - Teixeira Júnior, Ronaldo Rodrigues (2012)
The present work had as objective to test the effects of different general instructions on rule following. Eighteen college students were exposed to a modified match-to-sample task and divided in three groups, which differed in the presentation of preliminary instructions (complete, without passages about materials or without passages about consequences). Subjects of each group were divided in two experimental conditions, in which accurate and inaccurate instructions were presented. Results showed that absence of sections about materials in the instructions complicates the learning task while absence of sections about consequences decreases the variety of responses. Notwithstanding, all subjects that performed the task correctly followed both accurate and inaccurate instructions.